An Examination of the Mechanisms by which Neural Precursors Augment Recovery following Spinal Cord Injury: A Key Role for Remyelination. Issue 3 (April 2014) - Hawryluk, Gregory W. J.; Spano, Stefania; Chew, Derek; Wang, Shelly; Erwin, Mark; Chamankhah, Mahmood; Forgione, Nicole; Fehlings, Michael G.
The mechanisms by which neural precursor cells (NPCs) enhance functional recovery from spinal cord injury (SCI) remain unclear. Spinal cord injured rats were transplanted with wild-type mouse NPCs, shiverer NPCs unable to produce myelin, dead NPCs, or media. Most animals also received minocycline, cyclosporine, and perilesional infusion of trophins. Motor function was graded according to the BBB scale. H&E/LFB staining was used to assess gray and white matter, cyst, and lesional tissue. Mature oligodendrocytes and ED1 + inflammatory cells were quantitated. Confocal and electron microscopy were used to assess the relationship between the transplanted cells and axons. Pharmacotherapy and trophin infusion preserved gray matter, white matter, and oligodendrocytes. Trophin infusion also significantly increased cyst and lesional tissue volume as well as inflammatory infiltrate, and functional recovery was reduced. Animals transplanted with wild-type NPCs showed greatest functional recovery; animals transplanted with shiverer NPCs performed the worst. Wild-type NPCs remyelinated host axons. Shiverer NPCs ensheathed axons but did not produce MBP. These results suggest that remyelination by NPCs is an important contribution to functional recovery following SCI. Shiverer NPCs may prevent remyelination by endogenous cells capable of myelin formation. These findings suggest that remyelination is an important therapeutic target following SCI.